Pengaruh Kualitas Website Dan E-Wom (Electronic Word Of Mouth) Terhadap Keputusan Pembelian Online Pada Aplikasi Shopee (Studi kasus pada mahasiswa FEB Universitas Islam Malang) - Muhammad Rizqi Ar-rouf; N Rachma; Arini Fitri Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
This study aims to examine the effect of Website Quality and E-WOM (Electronic Word Of Mouth) on Purchase Decisions on the Shopee application. This research is a quantitative research with data collection techniques using a questionnaire. The sample in this study amounted to 104 respondents. The sampling technique used was the purposive sampling method. Primary data processing using multiple regression analysis. The results of this study indicate that the variables of website quality and e-WOM (electronic word of mouth) simultaneously affect purchasing decisions. Partially, the website quality variable has an effect on purchasing decisions, and the e-WOM (electronic word of mouth) variable has no effect on purchasing decisions.